An assessment of the appropriateness/effectiveness of the dominant leadership style in the public sector : a case of the Department of International Relations and Cooperation - Bhegu, Hlengiwe (Stellenbosch : Stellenbosch University, 2023)
Thesis (MPA)--Stellenbosch University, 2023.